For this case we must find an expression equivalent to:
[tex](x ^ {\frac {1} {2}} * y ^ {-\frac {1} {4}})^{-2}[/tex]
By definition of power properties we have to:
[tex](a ^ n) ^ m = a ^ {n * m}[/tex]
So:
[tex]x ^ {\frac {1 * -2} {2}} * y ^ {-\frac {1 * -2} {4}} =\\x ^ {\frac {-2} {2}} * y ^ {\frac {2} {4}} =\\x ^ {-1} *y ^ {\frac {1} {2}}[/tex]
We have by definition of properties of powers that:[tex]a ^ {-1} = \frac {1} {a ^ 1} = \frac {1} {a}[/tex]
Then, rewriting the expression:
[tex]\frac{y^{\frac{1}{2}}}{x}[/tex]
Answer:
[tex]\frac{y^{\frac{1}{2}}}{x}[/tex]